2015
DOI: 10.3109/1061186x.2015.1073295
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine and cancer immunotherapy – targeting immunosuppressive cells

Abstract: The search for pharmacological strategies to reach and impact on immunosuppressive cells is, currently, one of the most exciting areas in cancer immunology and clinical oncology. In this context, it is increasingly accepted that the success of these therapies will largely depend on the availability of appropriate drug delivery strategies. Considering the critical role that nanotechnology plays in the development of these novel therapies, the main goal of this article is to provide an overview of the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 187 publications
(160 reference statements)
0
17
0
Order By: Relevance
“…The data were representatives of three independent experiments and presented as the mean ± SD. *P < 0.05, **P < 0.01 and ***P < 0.001 vs control [37][38][39] Clinical researches also reveal the infiltration of M2-like TAMs is associated with treatment failure and poor prognosis in different cancers. 2,9,12 Thus, we have reasons to believe the potential anti-tumour effect of dioscin by regulating macrophage polarization.…”
Section: Isscus I Onmentioning
confidence: 96%
“…The data were representatives of three independent experiments and presented as the mean ± SD. *P < 0.05, **P < 0.01 and ***P < 0.001 vs control [37][38][39] Clinical researches also reveal the infiltration of M2-like TAMs is associated with treatment failure and poor prognosis in different cancers. 2,9,12 Thus, we have reasons to believe the potential anti-tumour effect of dioscin by regulating macrophage polarization.…”
Section: Isscus I Onmentioning
confidence: 96%
“…MDSCs and TAMs can facilitate the use of nanoparticles in anti-cancer immunotherapeutics due to their phagocytic ability (171). It was shown that in tumor-bearing mice peripherally administered with nanoparticles, the monocytic and polymorphonuclear MDSCs were preferentially targeted uptaking 10-fold more of these carrier materials compared to the tumor cells (172).…”
Section: Future Perspectives: Nanomedicine Approaches To Deplete Modmentioning
confidence: 99%
“…In contrast to the above-mentioned scenarios, a long circulation time is not a prerequisite for the passive targeting of organs such as spleen. Splenic accumulation of nanoparticles is of particular interest for the passive targeting of the immunotherapeutic payloads to the splenocytes, whose activation can exert substantial therapeutic effect in many disorders [ 281 ]. Furthermore, passive accumulation of the subcutaneously injected nanoparticles of 10–100 nm in the lymphatics provides a further platform for the optimal delivery of various vaccines and immunotherapeutics to their optimal site of action [ 282 ].…”
Section: Passive Targetingmentioning
confidence: 99%